Sistem Pendukung Keputusan Pemberian Sanksi Pelanggaran Kedisiplinan Guru Dalam Proses Belajar Mengajar Menggunakan Metode Elemination And Choice Translation Reality - Aulia Husna (Graha Mitra Edukasi, 2023)
Sanctions are actions (punishments) in order to force someone to follow the rules or to comply with the provisions of the law. The imposition of sanctions at SMKN 1 Lubuk Pakam is adjusted to the number of violations committed by the teacher by looking at the data that has been collected. Many problems occurred during the process of imposing sanctions, such as data on violations that were forgotten in the data, teachers who committed violations were not recorded because of family relationships or double data violations. This will give the impression that the sanctions are selective so that the sanctions given are not in accordance with the violations committed by the teacher. The solution that can be done to this problem is to build a decision support system to assist in sanctioning violations of teacher discipline in the on-target teaching and learning process using the method of elimination and choice translation reality. The results of this study can simplify and accelerate in determining the imposition of sanctions, so that this system can be used to assist the SMKN 1 Lubuk Pakam in making decisions to impose sanctions on teacher disciplinary violations in the teaching and learning process that are on target and are expected to overcome all weaknesses in determining the imposition of sanctions.